ANALISIS PENGARUH ANGGARAN PENDAPATAN DAN BELANJA DAERAH TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAWA TENGAH - Pusporini, Irma Dwi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.06.TAHUN 2020, 2020)
This study aims to examine the effect of employee expenditure, goods and service expenditure, and capital expenditure on economic growth in Central Java Province. The hypothesis proposed is that employee spending has a positive effect on economic growth, spending on goods and services has a positive effect on economic growth, and capital expenditure has a positive effect on economic growth. The sample in this study was a regency / city in Central Java Province. The technique of determining the sample using purposive sampling. This type of data is secondary data in the form of 2018 local government financial reports obtained from the Directorate General of Fiscal Balance's Website of the Ministry of Finance of the Republic of Indonesia and data from the Central Statistics Agency (BPS) Webside. Technical analysis of data using multiple regression analysis. The results showed that personnel expenditure and goods and services expenditure had a positive effect on economic growth, while capital expenditure did not have a positive effect on economic growth.